KEMAMPUAN TANAMAN KAYU APU (Pistia stratiotes) SEBAGAI MEDIA FITOREMEDIASI AIR BELERANG DENGAN PERLAKUAN AERASI UNTUK KUALITAS AIR PERTANIAN - Yosefina Mangera; Mega Ayu Yusuf (AGRICOLA, 2017)
Groundwater wells (sulfuric water) in Merauke is potentially high even in dry season. However, the high element of sulfur (S) in a plant can cause potion even death. The research is to determine the ability of lettuce (Pistia stratiotes) as a media of phytoremediation to decrease sulfur with an aeration treatment to fulfill the agricultural requirement. The treatment methods are closure surface of sulfuric acid with the lettuce. The treatments are namely without a closure, 25% closure, 50% closure, and 100% closure, where each treatment are using an aerator. The study is divided for into two stages. There are the early stage research (acclimatization) and the main research. Analysis of data includes the time and the corelation graph. On acclimatization stage, it was found that the concentration of SO4 was declining at 216 hours. The 50% of closure treatment showed that the lowest concentration of SO4 was at 81 mg /l. All of the treatments showed that the concentrations  of  H2S were declined on 48 hours on the main research.There were caused by the aerator that brings an oxidation process within the aeration. H2S oxidation produces SO4, so that the concentration of SO4 on control and all treatment have increased until the observation in 240 hours. From these results it can be concluded that the Pistia stratiotes is not required as phytoremediation agent in improved the water quality of sulfur. The award of oxygen (aeration) have been effective in reducing the concentration of S in the sulfur water to match the quality of agricultural water.